UPAYA PENYELESAIAN SENGKETA WILAYAH PERBATASAN DARAT INDONESIA – TIMOR LESTE DALAM PERPSPEKTIF HUKUM INTERNASIONAL - Randy Yusuf Taebenu; Yohanes Arman (INTELIGENSIA MEDIA, 2024)
In the 2017 Annual Press Statement of the Minister of Foreign Affairs, Minister of Foreign Affairs (Menlu) Retno LP Marsudi stated that Indonesia will accelerate the settlement of negotiations on Indonesia's territorial border issues with several neighboring countries, one of which is Timor Leste. Minister of Foreign Affairs Retno also emphasized that the settlement of Indonesia's border with Timor Leste will be carried out peacefully, without the threat of violence, and with full respect for international law. This article seeks to understand the border dispute between Indonesia and Timor Leste from the perspective of international relations. There are three strategies that can be taken by Indonesia in order to resolve this dispute, namely military confrontation, the use of formal institutions such as international organizations and the use of informal institutions, namely norms, beliefs, ideas and values. This article argues that to resolve the Noel Besi/Citrana and Bijael Sunan/Oben disputes, it is not enough to rely on international treaties/agreements alone, Indonesia needs to place more emphasis on the importance of understanding the norms, beliefs, ideas and values of indigenous peoples living in the disputed area. Certainly the combination of strategies for utilizing formal and informal institutions can accelerate the resolution of the Noel Besi/Citrana and Bijael Sunan/Oben disputes.